A CROSS-CULTURAL EXAMINATION OF ANIMAL SYMBOLS IN ENGLISH AND UZBEK (Modern education and development, 2025)
This article explores the symbolic meanings of animals in English and Uzbek languages, examining both shared and unique cultural associations. Animal symbols play a significant role in shaping linguistic expressions and cultural values, often reflecting societal views on characteristics such as strength, wisdom, and loyalty. By comparing common animal symbols, this study aims to highlight how English and Uzbek cultures attribute specific traits to animals, influencing idiomatic expressions and communication styles. Analyzing these symbolic meanings provides insight into the cultural mindsets and worldviews expressed through language in both English-speaking and Uzbek-speaking contexts.Ushbu maqola ingliz va o'zbek tillarida hayvon nomlarining ramziy ma'nolarini o'rganadi, umumiy va noyob madaniy assotsiatsiyalarni ko'rib chiqadi. Hayvon nomlari ramzlari til ifodalari va madaniy qadriyatlarni shakllantirishda muhim rol o'ynaydi, ko'pincha kuch, donolik va sadoqat kabi xususiyatlarga bo'lgan ijtimoiy qarashlarni aks ettiradi. Oʻxshash hayvon ramzlarini taqqoslash orqali, ushbu tadqiqot ingliz va o'zbek madaniyatlari hayvonlarga ma'lum xususiyatlar berishini, bu esa idiomatik ifodalar va muloqot uslublariga ta'sir ko'rsatishini ta'kidlashni maqsad qilgan. Ushbu ramziy ma'nolarni tahlil qilish, ingliz va o'zbek kontekstlarida til orqali ifodalangan madaniy fikrlash va dunyoqarashlar haqidagi tushunchalarni ochib beradi.